Utility of PROM Questionnaires: Correlation of Question Burden and Response Rate Among Surgically Treated Patients with Musculoskeletal Diseases - Vilkki, Karita; Äärimaa, Ville; Meronen, Saara; Kostensalo, Joel; Taskinen, Hanna-Stiina; Rantalaiho, Ida; Ryösä, Anssi; Pernaa, Katri; Laaksonen, Inari (Journal of clinical medicine, 2025)
Objectives: Patient-reported outcome measures (PROMs) constitute a patient-centered way to assess treatment outcomes in musculoskeletal diseases. In this study, we explored the factors affecting the response rate when systematically utilizing PROMs for operatively treated patients in a clinical setting. The purpose was to find factors that could be influenced to improve the response rates of questionnaires in the future. Methods: The data were collected from a large institutional registry, divided into seven sub-registries (hand, elbow, shoulder, back, hip, knee, and foot and ankle), by gathering demographic data and joint-specific and generic PROM results. The data were collected preoperatively, as well as postoperatively at 3 months and 1 year. We analyzed patient demographics, the questionnaire format, and the length of each questionnaire, which were hypothesized to be the factors associated with the response rate. Results: The study sample consisted of 2295 patients with operatively treated musculoskeletal conditions. A response rate of 60% or above was obtained for the whole patient cohort at all three time points, although not in all sub-registries. A higher number of questionnaire items (−0.021, p < 0.001) and the patients’ smoking status (−0.395, p = 0.002) were associated with a lower response rate. The response rate increased with the patient age up to 75 years and decreased thereafter. Conclusions: A suitable limit for the number of questions in a PROM questionnaire might be 50 to ensure the required 60% response rate to obtain generalizable results. Special effort should be made to improve the PROM response rate among the younger adult patient population.